"Only Wailing and Protesting"? Emotion Work and the Yishuv Controversy About the Anti-Nazi Boycott - Shoham, Hizky (AJS review, 2025)
Why did Jewish Palestine dissent from the global Jewish boycott of Nazi Germany in the 1930s? Whereas previous scholarship explains it with pragmatic considerations, this article draws on the "emotional turn" to explain the controversy within the Zionist movement and the Yishuv, and examines the roles played by the Zionist ethos of emotional restraint. Drawing on contemporary media and archival sources, the article examines the discourse about emotions that was part of the public debate about the boycott that raged in Palestine, and especially about the Haʿavarah (transfer) arrangement. This affair demonstrates that the relationships between emotions and political action are more complex than the simplistic dichotomy between "emotionality" and "practicality" that contemporaries employed and scholars have echoed. Further, it highlights how Jewish emotional life was politicized by the rise of Zionism.